Association of CYP11A1 Polymorphisms with Recurrent Pregnancy Loss in the Female Population of Punjab - Amanjot Kaur Rayat; Pallvi Thapar; Mandeep Kaur; Sukhjashanpreet Singh; Anupam Kaur (Journal of Human Reproductive Sciences)
Background: Recurrent pregnancy loss (RPL) is defined as the failure of two or more clinically recognised pregnancies before 20 weeks of gestation. The prevalence of clinically evident RPL is 1%–2% worldwide. The aetiologies of RPL include uterine anatomic anomalies, uncontrolled diabetes mellitus, untreated hypothyroidism, parental chromosomal abnormalities, antiphospholipid antibody syndrome, thrombophilia, genetic abnormalities and infections. Aims: This study was aimed at investigating the possible association between CYP11A1 (rs11632698) and (rs4077582) polymorphisms with RPL in the female population of Punjab. Settings and Design: The case– control study was conducted on 170 subjects, of which 80 RPL cases and 90 controls were analysed. Materials and Methods: Genotypic analysis was performed using the polymerase chain reaction – restriction fragment length polymorphism. Statistical Analysis Used: Pearson’s Chi-square test was used. Results: The genotypic frequency of CYP11A1 (rs11632698) A > G polymorphism was statistically significantly different amongst cases and controls (P = 0.00001). It was observed that the presence of the G allele might increase the risk of RPL. A Chisquare analysis of CYP11A1 (rs4077582) (P = 0.01) indicated a significant difference amongst the genotypes of cases and controls of RPL. Conclusion: CYP11A1 variants (rs11632698 and rs4077582) may be useful markers in determining the genetic susceptibility to the pathogenesis of RPL. Keywords: CYP11A1, recurrent miscarriage, recurrent pregnancy loss, rs11632698, rs4077582, spontaneous abortion.